GEOCHEMICAL CONSTRAINTS ON THE ORIGIN OF THE PERMIAN BAIMAZHAI MAFIC-ULTRAMAFIC INTRUSION, SW CHINA - Wang C.Y.; Zhou M.-F.; Keays R.R. (My University, 2006)
The ~260 Ma Baimazhai mafic-ultramafic intrusion is considered to be part of the Emeishan large igneous province and consists of orthopyroxenite surrounded by websterite and gabbro. The intrusion is variably mineralized with a massive sulfide ore body (~20 vol.%) in the core of the intrusion. Silicate rocks have Ni/Cu ratios ranging from 0.3 to 46 with majority less than 7 and are rich in LREE relative to HREE and show Nb and Ta anomalies in primitive mantle-normalized trace element patterns, with low Nb/Th (1.0-4.5) and Nb/La (0.3-1.0) ratios. Their ε Nd(t) values range from -3.3 to -8.4. Uniform Pd/Pt (0.7-3.5) and Cu/Pd (100,000-400,000) ratios throughout the intrusion indicate that all the sulfides in the rocks were formed in a single sulfide-saturation event. Modeling suggests that the Baimazhai rocks were formed when an Mg-rich magma became crustally contaminated in a deep-seated staging chamber. Crustal contamination (up to ~35%) drove the magma to S-saturation and forced orthopyroxene (Opx) onto the liquidus. The crystal-bearing magma forced out of the staging chamber was migrated by flow differentiation and consequently, the denser sulfide melt and the Opx crystals became centrally disposed in the flowing magma to form the Baimazhai intrusion. © Springer-Verlag 2006.
Keywords: Палеозой::Пермская; Paleozoic::Permian